The Effect of Taking Amino Acids Associated with Muscle Strength Training On the Development of Some Physiological Indicators In Badminton Players - Dakhil, Abeer; Essa, Ola (Journal of Physical Education, 2017)
The aim of the research was designing a nutritional program with amino acids well as designing exercises for muscular strength training for youth female badminton players. In addition to that the researcher aimed at identifying the effect of amino acid accompanied with muscular training on some physiological indicators in youth female badminton players. The researcher used the experimental method. The subjects were (7) youth female badminton players from the Armenian badminton club. Many physiological tests were conducted including PWC170 and Vo2Max. The data was collected and treated using proper statistical operations to conclude that amino acid accompanied with muscular ability training have a positive effect on some physiological indicators in female badminton players